2015
DOI: 10.1016/j.steroids.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Rapid proteasomal elimination of 3-hydroxy-3-methylglutaryl-CoA reductase by interferon-γ in primary macrophages requires endogenous 25-hydroxycholesterol synthesis

Abstract: HighlightsIFN-γ leads to the proteasomal degradation of HMGCR.IFN-γ and 25-HC can transcriptionally and post-translationally alter levels of HMGCR.The reduction of HMGCR through the action of IFN-γ requires the de novo synthesis of 25-HC by CH25H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 54 publications
1
17
1
Order By: Relevance
“…Instead, AMPK may be activated as a key upstream regulator for the upregulation of ATF3. More recently, it was reported that ATF3 induction by Toll-like receptors is strictly dependent on IFN-signalling33. In our study, naringenin failed to inhibit the activation of IRF3 or attenuate the production of IFN-β or RANTES.…”
Section: Discussioncontrasting
confidence: 50%
“…Instead, AMPK may be activated as a key upstream regulator for the upregulation of ATF3. More recently, it was reported that ATF3 induction by Toll-like receptors is strictly dependent on IFN-signalling33. In our study, naringenin failed to inhibit the activation of IRF3 or attenuate the production of IFN-β or RANTES.…”
Section: Discussioncontrasting
confidence: 50%
“…While JQ1 decreased the number of JQ1-sensitive cells as previously shown, no effects were induced in HepG2-R upon drug administration ( Figure 6B). Importantly, the restoration of cell proliferation observed in HepG2-R cells was completely abolished by 25-hydroxycholesterol (25OHC) treatment, a well-known methodological approach to mediate HMGCR degradation through the activation of a feedback mechanism [40]. Similar results were also obtained by blocking HMGCR activity with simvastatin, a potent inhibitor of cholesterol biosynthesis ( Figure 6C).…”
Section: Bet Inhibition Affects Cell Proliferation In a Cholesterol-dsupporting
confidence: 58%
“…Our data demonstrate, therefore, an IFN-elicited sequential regulation of the sterol metabolic network in which 25-HC provides an immediate, rapid mechanism for decreasing sterol biosynthesis and mediating antiviral effects. This involves a 25-HC blockade of SREBP2 translocation to the nucleus and the proteolytic degradation of HMGCR [ 18 , 52 ]. The effects of 25-HC are followed by miR-342-5p further promoting a more sustained fine-tuning of sterol metabolism and antiviral effects in the cell by targeting SREBF2 RNA and transcripts encoding select enzymes of the sterol biosynthesis pathway (e.g., IDI1 and SC4MOL ).…”
Section: Discussionmentioning
confidence: 99%